2014
DOI: 10.1002/tox.22096
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin protects human peripheral blood mononuclear cells from OTA‐induced oxidative stress, genotoxicity, and inflammation

Abstract: Ochratoxin A (OTA) is one of the most abundant food-contaminating mycotoxins world wide, and is detrimental to human and animal health. This study evaluated the protective effect of quercetin against OTA-induced cytotoxicity, genotoxicity, and inflammatory response in lymphocytes. Cytotoxicity determined by MTT assay revealed IC20 value of OTA to be 20 µM, which was restored to near control values by pretreatment with quercetin. Oxidative stress parameters such as antioxidant enzymes, LPO and PCC levels indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 50 publications
2
22
1
1
Order By: Relevance
“…However, the exact mechanism of OTA‐induced nephrotoxicity has not yet been completely understood. The results obtained in this study, in accordance with in vitro and in vivo studies (Abdel‐Wahhab, Aljawish, El‐Nekeety, Abdel‐Aziem, & Hassan, ; Ciarcia et al, ; Costa et al, ; Periasamy, Kalal, Krishnaswamy, & Viswanadha, ), confirmed that the toxic effect of OTA on the kidney found both on the functional level and from the histopathology of view is mediated by oxidative stress. It has been shown that OTA acts by inhibiting the nuclear factor, which would affect both the synthesis and the recycling of glutathione and also the activity of oxidoreductases thus making the tissue more vulnerable to oxidative stress (Jennings, Limonciel, Felice, & Leonard, ; Limonciel & Jennings, ).…”
Section: Discussionsupporting
confidence: 90%
“…However, the exact mechanism of OTA‐induced nephrotoxicity has not yet been completely understood. The results obtained in this study, in accordance with in vitro and in vivo studies (Abdel‐Wahhab, Aljawish, El‐Nekeety, Abdel‐Aziem, & Hassan, ; Ciarcia et al, ; Costa et al, ; Periasamy, Kalal, Krishnaswamy, & Viswanadha, ), confirmed that the toxic effect of OTA on the kidney found both on the functional level and from the histopathology of view is mediated by oxidative stress. It has been shown that OTA acts by inhibiting the nuclear factor, which would affect both the synthesis and the recycling of glutathione and also the activity of oxidoreductases thus making the tissue more vulnerable to oxidative stress (Jennings, Limonciel, Felice, & Leonard, ; Limonciel & Jennings, ).…”
Section: Discussionsupporting
confidence: 90%
“…Despite the numerous strategies developed to reduce OTA-induced nephrotoxicity, this mycotoxin mechanism of action remains complex and unknown. However, in recent years, several in vivo and in vitro studies have recognized that the induction of the oxidative stress induced by OTA exposure is considered one of the mechanisms responsible for its toxicity [30][31][32][33]. Thus, the administration of antioxidants that counteract oxidative stress may protect kidneys from damage.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that oxidative stress occurs due to an imbalance between oxidant and antioxidant systems, which could be due to elevated free radical generation and decreased antioxidant activity. Several studies suggest that both in vitro and in vivo OTA exposure results in the overproduction of free radicals [22,32,33], causing damage to cell constituents such as membrane lipids. Therefore, the main antioxidant enzymes, such as CAT, SOD and GPx, play a crucial role in protection against oxidative stress [39].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies indicated that quercetin could ameliorate OTA‐induced oxidative stress in different types of cells such as human peripheral blood mononuclear cells, HepG2 cells, and Vero cells, and the Nrf2 pathway might play essential roles in the regulation of quercetin on Vero cell line (Periasamy, Kalal, Krishnaswamy, & Viswanadha, ; Ramyaa & Padma, ; Ramyaa, Krishnaswamy, & Padma, ). Similarly, quercetin at 5 μM was found to offer a protective effect against the cellular toxicity of α‐ZOL (180 μM) or β‐ZOL (300 μM), through inhibiting oxidative stress, endoplasmic reticulum stress and cell apoptosis via a mitochondria‐dependent pathway (Ben Salem, Prola et al., ).…”
Section: Food Compounds Especially Those Of Plant Origin For Prevenmentioning
confidence: 99%